Influence of operational sex ratio and male age on mating competition intensity in reindeer (Rangifer tarandus). Issue 1 (2nd January 2023) - Driscoll, Jeffrey G.; Alo, Franco M.; Paoli, Amélie; Weladji, Robert B.; Holand, Øystein; Kumpula, Jouko; Soveri, Timo
Abstract : The operational sex ratio (OSR), the ratio of sexually active males to sexually receptive females, is one of the main measures used to predict the intensity and direction of mating competition, influencing the opportunity for sexual selection. Here, we conducted the first experimental study to investigate how OSR and male age impacts the intensity of mating competition in reindeer ( Rangifer tarandus ), under semi-natural conditions during the rut. We manipulated OSR on two levels in two enclosures, a female biased treatment (3♂:6♀ = OSR 0.5) and a sex balanced treatment (3♂:3♀ = OSR 1), over 2 years with males from two age groups, and with females of various ages. We found some support for prevailing OSR theory, notably with female intrasexual competition occurring at lower frequencies in OSR 1 than OSR 0.5, and male intrasexual competition occurring at higher frequencies in the older male age group. Courtship behaviour was found to occur at higher frequencies in OSR 1 than OSR 0.5; however, there was no effect of male age. To successfully pass on genes to the next generation, one needs access to mates and winning a competitive bout is not always indicative of successfully accomplishing gene flow. Studies on OSR have the potential to help us understand the drivers behind sexual competition and how best to predict breeding outcomes during a rut.